Dynamical Analysis of a Supercapacitor Based Multilevel Inverter - LAKBIR, Jamila; BOUDOUDOUH, Soukaina; BOUATTANE, Omar (Procedia computer science, 2024)
This paper deals with a dynamical analysis of a supercapacitor based multilevel inverter. In Fact, applications for multi-level inverters based on supercapacitors include uninterruptible power supplies (UPS), grid-tied renewable energy systems, electric vehicles, and other power conversion systems where high-power quality and rapid energy transfer are important. These systems are the subject of ongoing research and development in the field of power electronics and energy storage, as they have the potential to enhance the performance and efficiency of various electrical and electronic applications. However, If the input voltage sources are fixed, this can limit the flexibility of the inverter, especially in terms of regulating the output voltage and adapting to load variations. This study is focused on the dynamic analyses which is crucial for designing, optimizing, and verifying the performance of supercapacitor-based multi-level inverters in various applications. Hence, the behaviour of the system was studied on a resistive load, material calculations showing the functioning of the circuit as well as simulations were performed for the positive phase of the sinusoid at the terminals of the charge.